RESISTÊNCIA INSTITUCIONAL DO MERCOSUL FRENTE AOS MOVIMENTOS DE RUPTURA DEMOCRÁTICA SUL-AMERICANOS - Rogério Santos da Costa (Universidade Federal do Maranhão, 2018)
This article aims to discuss the institutional resistance of Mercosur to the ad- vance of conservatism in South America, especially in relation to the post-coup foreign policy of 2016 in Brazil that culminates in the suspension of Venezuela from the bloc in 2017. Taking as a parameter the policy the objective of the Lula Government’s foreign policy is to contribute to the understanding of the limitations and institutional needs of Mercosur, capable of achieving greater resistance to changes in government or democratic ruptures. Based on two premises, dependence on trajectory and institutional eﬀectiveness, the work is the result of documentary research, interviews and a literature review. It is concluded that, despite the advances in the Lula era, Mercosur did not change its trajectory to the point of giving eﬀectiveness to its objectives and creating institutional resistance.